HUBUNGAN ANTARA KEJADIAN ANEMIA DENGAN STATUS GIZI PADA REMAJA PUTRI : A SYSTEMATIC REVIEW - Adyani, Asta (Sinar : Jurnal Kebidanan, 2023)
Objective: Malnutrition and health problems can damage the quality of human resources. Adolescent girls have a higher risk of developing anemia compared to adolescent boys because adolescent girls experience incorrect menstrual cycles and eating habits. Nutritional imbalance, especially in the form of macro and micronutrient deficiencies, such as eating high-calorie but nutritious foods (high in fat, carbohydrates, and sugar), can cause fat accumulation and disrupt metabolism. Absorption of iron nutrients, causing anemia. This research aimed to determine whether there was a relationship between the incidence of anemia and nutritional status in adolescent girls.   Methods: Articles were collected by searching databases via Ebsco Host, Google Scholar, and PubMed. Only articles with a cross-sectional research design and those with full text will be included in this review. There were 12,213 results for articles with the keywords "The Relationship of Anemia" AND "Adolescents Nutrition Status" OR "Female Teenagers Nutrition." After filtering again by looking for articles from 2013 to 2020, there were 1,602 articles, and only five articles were very relevant and met the inclusion and exclusion criteria. Results: Three articles show a relationship between the incidence of anemia and nutritional status in young women, and two other articles show no significant relationship between the incidence of anemia and nutritional status because the majority of young women studied in this area have normal nutritional status. Conclusion: Most research results conclude that there is a known relationship between nutritional intake and the incidence of anemia in adolescent girls